Gastrointestinal disorders after immunosuppression: an experimental model to evaluate the influence of monotherapy on motility parameters - Dall'Agnol, Denize Jussara Rupolo [UNESP]; Corá, Luciana Aparecida; Teixeira, Maria do Carmo Borges; de Lima, Maysa Bruno; Gama, Loyane Almeida [UNESP]; Miranda, José Ricardo de Arruda [UNESP]; Américo, Madileine Francely (Wiley, 2017)
New Findings: What is the central question of this study? The aim was to propose an animal model for investigating the effects of immunosuppressive monotherapy on gastrointestinal motility using a non-invasive biomagnetic technique. What is main finding and its importance? In our experimental study, immunosuppressive drugs currently in use accelerated gastric emptying whilst increasing the frequency and amplitude of gastric contractions after treatment, except for Mycophenolate and azathioprine. Alternating current biosusceptometry is a useful tool to evaluate side-effects of drugs on the gastrointestinal tract, which will help in understanding the symptoms and improving clinical management of patients. The aim was to propose an animal model for investigating the effects of immunosuppressive monotherapy on gastrointestinal motility using a non-invasive biomagnetic technique. Male Wistar rats were randomly distributed into the following treatment groups: ciclosporin, tacrolimus, prednisone, sirolimus, mycophenolate mofetil, everolimus, azathioprine and control. Each animal was treated for 14 days by gavage with dosages ranging from 1 to 20 mg kg−1 day−1 considering the area-to-volume ratio and hepatic metabolism. Gastrointestinal transit and gastric contractility measurements were evaluated by alternating current biosusceptometry before and after treatment. Gastric emptying was faster in animals treated with tacrolimus, prednisone, sirolimus and everolimus compared with control animals (126.7 ± 12.7 min). There was a significant increase in the frequency of contractions after ciclosporin, tacrolimus, azathioprine and sirolimus treatment compared with control animals (4.6 ± 0.3 cycles min−1). Increases in the amplitude of contraction were observed after treatment with tacrolimus, sirolimus and everolimus compared with control rats (34.9 ± 6.0 dB). The results showed that our animal model was suitable for demonstrating that most immunosuppressive drugs currently in use impaired at least one gastrointestinal motility parameter. As a non-invasive technique, alternating current biosusceptometry is a potentially useful tool for evaluation of side-effects of drugs in gastrointestinal tract, helping us to understand the symptoms to improve clinical management of patients.
Keywords: AC biosusceptometry; gastrointestinal motility; immunosuppressants